IMPLEMENTATION OF THE INAPORNET SYSTEM IN IMPROVING SHIP LICENSING SERVICES IN THE UPP MOLAWE OFFICE AREA - Byo, Dardi Ode; Aedy, Hasan; Razak, Abdul (Penelitian dan Pengembangan Ilmu, 2024)
The application of digital technology has brought significant changes in improving the efficiency of public services, including the transportation sector. In the ship licensing service, the Inaportnet System at the UPP Molawe Office is expected to facilitate a faster and more efficient administrative process. However, in its implementation, the system faces technical constraints, such as network instability and lack of user understanding, which hinder the achievement of optimal efficiency. This study uses a descriptive qualitative approach with in-depth interviews with three informants who have a direct role in the management and implementation of the Inaportnet System. The results show that although Inaportnet has improved the efficiency of ship licensing services, some challenges such as network constraints and user literacy still need to be overcome to achieve full optimization. The implications of this study emphasize the importance of improving network infrastructure and continuous education for users to support the sustainability of digital services in the transportation sector.